CHILD FRIENDLY URBAN NEIGHBORHOOD IN PUTRAJAYA, MALAYSIA - Hashim, Habsah; Hashim, Siti Fatimah; Shuib, Kamarul Bahrain (PEOPLE: International Journal of Social Sciences, 2019)
Putrajaya, Malaysia was developed by Putrajaya Corporation with a purpose of achieving sustainability through maintaining a balance between the social aspect, the environment and the economy. The planning was based on two fundamental concepts i.e. city in the garden and the intelligent city. In line with this target, various initiatives to create a better quality of life for the residents had been incorporated into the planning and design of the neighborhoods. Among these initiatives include consideration towards the needs of children in their daily routine. This paper discusses the findings of a study done to assess the residential environment in Precinct 11 Putrajaya in terms of the level of child-friendliness. The study evaluates five common areas where children often goes to within an urban neighborhood and its surroundings. The five areas are the residential blocks, parks and recreation spaces, school environment, commercial centers and community facilities area. Primary data were gathered through guided observation, capturing of images through photography and also face-to-face interviews with adults who have children aged between 7 to 12 years old at the selected locations during a two-week long field survey. The observation checklist and the questionnaire were based on indicators that reflect child-friendliness in terms of the social and physical environments. The study found that the physical environments in most areas are responsive to children’s needs. However, the social interactions in Putrajaya Precinct 11 neighborhoods are found to be limited and confined. Based on the findings and indicators of a child-friendly environment, several suggestions are outlined at the end of the paper in an effort to promote a better quality of life for children in the urban neighborhoods.